2016
DOI: 10.1515/polyeng-2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas counter pressure on shrinkage and residual stress for injection molding process

Abstract: Plastic products are common in contemporary daily lives. In the plastics industry, the injection molding process is advantageous for features such as mass production and stable quality. The problem, however, is that the melt will be affected by the residual stress and shrinkage generated in the process of filling and cooling; hence, defects such as warping, deformation, and sink marks will occur. In order to reduce product deformation and shrinkage during the process of molding, the screw of the injection mold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Santis et al [16] explored the effects of suppression, time, and geometric constraints on the contraction of semi-crystalline polymers with strain gauges. Chen SC et al [17,18] applied gas backpressure to reduce the shrinkage of parts during injection molding. Qi et al [19] found that mixing of polypropylene copolymers can effectively reduce the molding shrinkage of isletic polypropylene.…”
Section: Defect Detection For the Injection Molding Processmentioning
confidence: 99%
“…Santis et al [16] explored the effects of suppression, time, and geometric constraints on the contraction of semi-crystalline polymers with strain gauges. Chen SC et al [17,18] applied gas backpressure to reduce the shrinkage of parts during injection molding. Qi et al [19] found that mixing of polypropylene copolymers can effectively reduce the molding shrinkage of isletic polypropylene.…”
Section: Defect Detection For the Injection Molding Processmentioning
confidence: 99%
“…[2] Fig. 1 Material flow in the mold [11] Test Injection Mold for Thermoplastic Elastomers Fig. 2 Testing injection mold for thermoplastic elastomers 1 -insulating plates, 2 -clamping plates, 3 -anchor plates, 4 -guiding elements, 5 -ejector plate, 6 -supporting plates, 7 -cavity plate, 8 -special sprue puller, 9 -lifting eye bolt, 10 -testing plate, 11 -sprue bushing, 12 -cooling nipple, 13 -ejector rod The test injection mold was a simple construction with changeable plates as well as gate size.…”
Section: Injection Molding Of Polymersmentioning
confidence: 99%
“…3 On the other hand, when the shear flow aligns the macromolecular chains, residual stress may be generated when the orientation freezes to form an unbalanced conformation. 4,5 The release of residual stress may lead to stress cracking, warping deformation or fatigue failure. 6,7 Therefore, controlling the shear flow in the injection molding process is very important to the conformation and properties of the polymer material.…”
Section: Introductionmentioning
confidence: 99%
“…The shearing effect during the injection process can untie the molecular chain and improve the filling flow 3 . On the other hand, when the shear flow aligns the macromolecular chains, residual stress may be generated when the orientation freezes to form an unbalanced conformation 4,5 . The release of residual stress may lead to stress cracking, warping deformation or fatigue failure 6,7 .…”
Section: Introductionmentioning
confidence: 99%